Method for efficiently preparing MAX-phase metal carbonitride through microwave molten salt

Through microwave molten salt technology, the problems of long reaction time and single product morphology during the preparation of MAX phase materials are solved, and the rapid and efficient preparation and morphology control of MAX phase materials are achieved, which is suitable for industrial production.

CN119683575APending Publication Date: 2025-03-25KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411898428.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing MAX phase material preparation process has a long reaction time and a single product and morphology, which is difficult to meet the needs of large-scale industrial production.

Method used

The method of efficient preparation of MAX phase metal carbon nitrides is adopted for microwave molten salts, and the preparation of MAX phase materials can be achieved through grinding, microwave drying and microwave molten salt synthesis steps.

Benefits of technology

It realizes the rapid and efficient preparation of MAX phase materials, can control the morphology and types of materials, is suitable for large-scale industrial production, and has a safe, efficient, clean and environmentally friendly process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683575A_ABST
    Figure CN119683575A_ABST
Patent Text Reader

Abstract

The invention discloses a method for efficiently preparing MAX-phase metal carbonitride through microwave molten salt, and relates to the technical field of synthesis and preparation of new materials. The preparation method comprises the following steps: selecting several of M-site metal, A-site metal, AlN, a carbon material and inorganic salt according to a target product, carrying out one-step microwave molten salt heating to obtain a mixed product, washing the product with deionized water to remove the inorganic salt, and drying the solid product after washing to obtain the required MAX phase material. According to the method for efficiently preparing the MAX-phase metal carbonitride through microwave molten salt, the MAX-phase material with the controllable morphology structure is prepared, the morphology structure characteristics are obvious, the reaction is rapid, the method is simple and efficient, and industrial production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new material synthesis and preparation, and in particular to a method for efficiently preparing MAX phase metal carbonitride using microwave molten salt. Background Art

[0002] MAX phase material is a ternary layered ceramic material with a hexagonal structure, in which M is a transition metal element, A is a main group element, and X is a C or N element. In the MAX phase material, the M-position atom and the X-position atom are connected by a strong covalent bond to form an MXM covalent bond, so that the MAX phase material retains some of the physical properties of MX, such as high strength and elastic modulus, good thermal stability, small expansion coefficient, strong acid and alkali corrosion resistance, and good high-temperature oxidation resistance. On the other hand, the MX structure and the A atom are bonded by a weaker MA metal covalent bond, so that the MAX phase material has good processability while also having some of the properties of the A layer metal, such as electrical conductivity, thermal conductivity and ductility. Given the characteristics of MAX phase materials that combine the properties of ceramics and metals, MAX phase materials have great application potential in many high-tech fields such as aerospace, high-speed rail, nuclear industry, radar absorption and stealth.

[0003] At present, most of the research on the preparation of MAX phase materials at home and abroad is to mix the raw materials, cold press them into shape, and then sinter them at high temperature. This type of method is not suitable for the efficient and rapid preparation of MAX phase powder materials. Related literature reports that the morphology and structure of MAX phase materials have a huge impact on their physical and chemical properties. CN202210466122.4 discloses a hollow MAX phase powder with controllable morphology and a preparation method thereof. Specifically, amorphous carbon powder and inorganic mixed salt are first subjected to molten salt heating treatment, and then the M-position metal powder, A-position metal powder and inorganic mixed salt are mixed and subjected to low-temperature molten salt heating treatment, and then the reaction products obtained in the two steps are mixed, and high-temperature molten salt heating reaction treatment is carried out to finally obtain a hollow MAX phase powder with controllable morphology. However, this molten salt technology requires three-step molten salt treatment, and the reaction time is long, which cannot meet the needs of efficient industrial production of high-quality MAX phase materials.

[0004] Therefore, it is crucial to develop a simple and efficient method for structural design and morphology control of MAX phase materials to meet the needs of mass production of high-quality MAX phase materials. Summary of the invention

[0005] The purpose of the present invention is to provide a method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt, so as to solve the problems existing in the preparation process of existing MAX phase materials, such as long reaction time, single product and morphology, and difficulty in meeting the requirements of large-scale industrial production.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for efficiently preparing MAX phase metal carbonitrides by microwave molten salt, characterized in that it comprises the following steps:

[0007] S1. Weigh several of the M-site metal powder, A-site metal powder, AlN powder, carbon material, and inorganic salt into a mortar, add anhydrous ethanol, and grind to obtain material a. The material a is placed in a ball mill and ball-milled until uniformly mixed to obtain material b. Different types and proportions of raw materials can be selected according to the desired MAX phase material type and composition to achieve MAX phase material type and morphology control;

[0008] S2. Rapidly dry material b in a microwave oven to remove anhydrous ethanol to obtain material c;

[0009] S3. The mixed material c is placed in a microwave oven under a protective atmosphere for molten salt synthesis, and selective microwave activation heating is used to achieve rapid and controllable preparation of MAX phase materials;

[0010] S4. Take out the mixed material c after the reaction in S3, add 5 to 8 times the volume of deionized water to remove inorganic salts, filter out the solid product, wash it repeatedly with deionized water and dry it, and dry the solid product to obtain a black powder, which is the prepared MAX phase material.

[0011] A further technical solution is that in step S1, the M-site metal powder is one or more of Ti, V, Cr, Mo, and Nb, the A-site metal is one or two of Al and Ga, the carbon material is one or more of layered graphite, spherical graphite, amorphous carbon powder, and carbon fiber, and the inorganic salt is one or two of NaCl and KCl.

[0012] A further technical solution is that in step S1, the molar ratio of the M-site metal, the A-site metal, AlN, the carbon material, NaCl, and KCl is (2-4): (0.1-1): (0.1-1): (0.1-3): (1-6): (1-6), and the amount of anhydrous ethanol added is 200-400 ml / mol of the M-site metal.

[0013] A further technical solution is that the total molar number of the M-site metal in the 211 phase is 2, the total molar number in the 312 phase is 3, the total molar number in the 413 phase is 4, the total molar number of the A-site metal and AlN is 1, the purity of the M-site metal powder is 99% to 99.99%, the purity of the A-site metal powder is 99% to 99.99%, and the purity of the AlN powder is 99% to 99.99%.

[0014] A further technical solution is that in step S1, the rotation speed of the ball milling process is 100-400 r / min, and the ball milling time is 1-2 h.

[0015] A further technical solution is that in step S2, the microwave heating power is 500-800 W, the microwave frequency is 2450±50 MHz, and the heating time is 10-30 min.

[0016] A further technical solution is that in step S3, the reaction temperature is 1100-1300°C, the heating rate is 30-50°C / min, the insulation time is 5-30min, the microwave heating power is 800-5000W, the microwave frequency is 2450±50 or 915±50MHz, and the protective atmosphere is argon or nitrogen.

[0017] A further technical solution is that the drying in step S4 is carried out using a blast drying oven, the drying temperature is 60-90° C., the drying time is 30-60 min, and the residual water content in the material after drying is 1-3%.

[0018] Reaction mechanism:

[0019] Preparation of MAX phase materials

[0020] Ti+C→TiC(1)

[0021] 3Ti+TiC+AlN+Al→2Ti2AlC 0.5 N 0.5 (2)

[0022] According to the target product, several of M-site metal, A-site metal, AlN, carbon material and inorganic salt are selected, microwaves are directly applied to carbon material (carbon fiber, spherical graphite, etc.), and carbon material rapidly changes from crystallization to amorphous state under the synergistic effect of microwave and molten salt, which promotes the generation of metal carbide intermediate phase, shortens the reaction steps and process, and obtains mixed product by one-step microwave molten salt heating, and washes the product with deionized water to remove inorganic salt, and MAX phase material is obtained by drying the solid product after washing. The present invention obtains MAX phase material by a method for efficiently preparing MAX phase metal carbonitride with microwave molten salt, which has rapid reaction, can realize the morphology and type control of MAX phase material, and the method is simple and efficient, and easy to industrialize.

[0023] Compared with the prior art, the beneficial effects of the present invention are: microwave heating is used to directly act on the carbon material and quickly heat up, so that the inorganic salt and the like quickly enter a molten state, and the molten salt provides a uniform polar liquid phase environment for the reaction, thereby reducing the reaction activation energy. Under the action of microwave molten salt, the carbon material quickly changes from a crystalline state to an amorphous state and forms a metal carbide intermediate phase, shortening the reaction steps, and realizing efficient and rapid MAX material structure and morphology regulation. Carbon materials can be selected according to the desired MAX phase material morphology to obtain fibrous and spherical MAX phase materials (Examples 1 and 2), and the M-position metal type is adjusted to obtain different types of MAX phase materials (Example 3), realizing precise regulation of MAX phase morphology and type. The reaction is carried out under a protective atmosphere, the MAX phase material has obvious morphological characteristics, and the entire process is safe, efficient, clean, environmentally friendly, and low energy consumption is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The fibrous Ti2AlC obtained in Example 1 and Comparative Example 1 0.5 N 0.5 XRD pattern of .

[0025] Figure 2 The fibrous Ti2AlC 0.5 N 0.5 SEM electron microscope image.

[0026] Figure 3 The spherical Ti2AlC obtained in Example 2 0.5 N 0.5 SEM electron microscope image.

[0027] Figure 4 The spherical V2AlC obtained in Example 3 0.5 N 0.5 XRD pattern of .

[0028] Figure 5 The spherical V2AlC obtained in Example 3 0.5 N 0.5 SEM electron microscope image. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] Example 1

[0031] The raw materials were weighed according to the amounts of 19.14 g Ti powder, 2.69 g Al powder, 4.1 g AlN, 1.2 g carbon fiber, 46.7 g NaCl, and 59.6 g KCl.

[0032] (1) First, the above raw materials were placed in a mortar, and 120 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 300 r / min for 1 h until mixed evenly to obtain material b.

[0033] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 600 W, the microwave frequency was 2450±50 MHz, and the heating time was 30 minutes to obtain material c.

[0034] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1100°C, a microwave power of 3000 W, a microwave frequency of 2450±50 MHz, a heating rate of 30°C / min, and a holding time of 10 min.

[0035] (4) The reactants were taken out, and deionized water 5 times the volume of the materials was added to remove inorganic salts. The solid product was filtered out, and it was repeatedly washed with deionized water for 3 times and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 60°C and a drying time of 60 min. After drying, the residual water content in the material was 1%, and the treated reaction product MAX phase material was obtained: fibrous Ti2AlC 0.5 N 0.5 .

[0036] Example 2

[0037] The raw materials were weighed according to the amounts of 19.14 g Ti powder, 2.69 g Al powder, 4.1 g AlN, 1.2 g spherical graphite, 46.7 g NaCl, and 59.6 g KCl.

[0038] (1) First, the above raw materials were placed in a mortar, and 100 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 300 r / min for 1 h until mixed evenly to obtain material b.

[0039] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 800 W, the microwave frequency was 2450±50 MHz, and the heating time was 20 minutes to obtain material c.

[0040] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1150°C, a microwave power of 4000 W, a microwave frequency of 2450±50 MHz, a heating rate of 40°C / min, and a holding time of 15 min.

[0041] (4) The reactants were taken out, and deionized water 5 times the volume of the materials was added to remove inorganic salts. The solid product was filtered out, and it was repeatedly washed with deionized water for 3 times and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 60°C and a drying time of 60 min. After drying, the residual water content in the material was 1.5%, and the treated reaction product MAX phase material was obtained: spherical Ti2AlC 0.5 N 0.5 .

[0042] Example 3

[0043] The raw materials were weighed according to the amounts of 20.3 g of V powder, 2.69 g of Al, 4.1 g of AlN, 1.2 g of spherical graphite, 46.7 g of NaCl, and 59.6 g of KCl.

[0044] (1) First, place the above raw materials in a mortar, add 100 ml of anhydrous ethanol and grind to obtain material a. Place material a in a ball mill and mill at 200 r / min for 1.5 h until mixed evenly to obtain material b.

[0045] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 700 W, the microwave frequency was 2450±50 MHz, and the heating time was 25 minutes to obtain material c.

[0046] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1200°C, a microwave power of 4000 W, a microwave frequency of 2450±50 MHz, a heating rate of 40°C / min, and a holding time of 20 min.

[0047] (4) The reactants were taken out, and deionized water 5 times the volume of the materials was added to remove inorganic salts. The solid product was filtered out, and it was repeatedly washed with deionized water for 3 times and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 60°C and a drying time of 60 min. After drying, the residual water content in the material was 1.2%, and the treated reaction product MAX phase material was obtained: spherical V2AlC 0.5 N 0.5 .

[0048] Example 4

[0049] The raw materials were weighed according to the amounts of 20.7 g of Cr powder, 6.97 g of Ga powder, 4.1 g of AlN, 1.2 g of layered graphite, 46.7 g of NaCl, and 59.6 g of KCl.

[0050] (1) First, the above raw materials were placed in a mortar, and 120 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 400 r / min for 1 h until mixed evenly to obtain material b.

[0051] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 800 W, the microwave frequency was 2450±50 MHz, and the heating time was 20 minutes to obtain material c.

[0052] (2) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1300°C, a microwave power of 5000 W, a microwave frequency of 2450±50 MHz, a heating rate of 50°C / min, and a holding time of 30 min.

[0053] (3) The reactants were taken out, and deionized water 5 times the volume of the materials was added to remove inorganic salts. The solid product was filtered out, and washed repeatedly with deionized water for 3 times and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 60°C and a drying time of 60 min. After drying, the residual water content in the material was 1.8%, and the treated reaction product MAX phase material was obtained: Cr2Ga 0.5 Al 0.5 C 0.5 N 0.5 .

[0054] Example 5

[0055] The raw materials were weighed according to the amounts of 19.1 g of Mo powder, 18.5 g of Nb powder, 6.97 g of Ga powder, 4.1 g of AlN, 1.2 g of spherical graphite, 46.7 g of NaCl and 59.6 g of KCl.

[0056] (1) First, the above raw materials were placed in a mortar, and 150 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 400 r / min for 1 h until mixed evenly to obtain material b.

[0057] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 800 W, the microwave frequency was 2450±50 MHz, and the heating time was 20 minutes to obtain material c.

[0058] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1300°C, a microwave power of 4000 W, a microwave frequency of 2450±50 MHz, a heating rate of 40°C / min, and a holding time of 30 min.

[0059] (4) The reactants were taken out, and deionized water 5 times the volume of the materials was added to remove inorganic salts. The solid product was filtered out, and washed repeatedly with deionized water for 3 times and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 60°C and a drying time of 60 min. After drying, the residual water content in the material was 1.8%, and the treated reaction product MAX phase material was obtained: spherical MoNbGa 0.5 Al 0.5 C 0.5 N0.5 .

[0060] Comparative Example 1

[0061] The raw materials were weighed according to the amounts of 19.14 g Ti powder, 2.69 g Al powder, 4.1 g AlN, 1.2 g carbon fiber, 46.7 g NaCl, and 59.6 g KCl.

[0062] (4) First, the above raw materials were placed in a mortar, and 120 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 300 r / min for 1 h until mixed evenly to obtain material b.

[0063] (5) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 800 W, the microwave frequency was 2450±50 MHz, and the heating time was 20 minutes to obtain material c.

[0064] (6) Material c was transferred to a conventional heating furnace for molten salt synthesis under argon atmosphere, with a reaction temperature of 1100°C and a holding time of 4 h.

[0065] (4) The reactants were taken out, and deionized water 5 times the volume of the materials was added to remove inorganic salts. The solid product was filtered out, and it was repeatedly washed with deionized water for 3 times and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 60°C and a drying time of 60 min. After drying, the residual water content in the material was 1%, and the treated reaction product MAX phase material was obtained: fibrous Ti2AlC 0.5 N 0.5 .

[0066] The product performance analysis in the above embodiment is shown in the figure, where: Figure 1 Ti2AlC was prepared for Example 1 and Comparative Example 1. 0.5 N 0.5 XRD spectrum, from which it can be seen that the product obtained by microwave molten salt has higher purity and shorter reaction time than that obtained by conventional heating molten salt; Figure 2 Ti2AlC was prepared for Example 1 0.5 N 0.5 The SEM electron microscope image shows that the product has a fibrous morphology; Figure 3 Spherical Ti2AlC was prepared for Example 2 0.5 N 0.5 The SEM electron microscope image shows that the product is obviously spherical. Figure 4-5 Spherical V2AlC was prepared for Example 3 0.5 N 0.5The XRD spectrum and SEM electron microscope image show that the product is obviously spherical and has high purity. This proves that the method has significant advantages in preparation efficiency and material morphology control, and can achieve efficient and rapid preparation of high-quality MAX phase materials to meet the needs of different fields such as aerospace, energy catalysis, and electromagnetic wave absorption.

[0067] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt, characterized in that The steps include: S1. Weigh several metal powders at the M position, metal powders at the A position, AlN powder, carbon materials, and inorganic salts in a mortar, add anhydrous ethanol, grind to obtain material a, and place material a in a ball mill until mixed to obtain material b; S2. Rapidly dry material b in a microwave oven to remove anhydrous ethanol to obtain material c; S3. The mixed material c is placed in a microwave oven under a protective atmosphere for molten salt synthesis, and selective microwave activation heating is used to achieve rapid and controllable preparation of MAX phase materials; S4. Take out the mixed material c after the reaction in S3, add 5 to 8 times the volume of deionized water to remove inorganic salts, filter out the solid product, wash it repeatedly with deionized water and dry it, and dry the solid product to obtain a black powder, which is the prepared MAX phase material.

2. The method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt according to claim 1, characterized in that: In step S1, the M-site metal powder is one or more of Ti, V, Cr, Mo, and Nb, the A-site metal is one or two of Al and Ga, the carbon material is one or more of layered graphite, spherical graphite, amorphous carbon powder, and carbon fiber, and the inorganic salt is one or two of NaCl and KCl.

3. The method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt according to claim 1, characterized in that: In the step S1, the molar ratio of the M-site metal, the A-site metal, AlN, the carbon material, NaCl, and KCl is (2-4): (0.1-1): (0.1-1): (0.1-3): (1-6): (1-6), and the amount of anhydrous ethanol added is 200-400 ml / mol of the M-site metal.

4. The method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt according to claim 1, characterized in that: The total molar number of the M-site metal in the 211 phase is 2, the total molar number in the 312 phase is 3, the total molar number in the 413 phase is 4, the total molar number of the A-site metal and AlN is 1, the purity of the M-site metal powder is 99% to 99.99%, the purity of the A-site metal powder is 99% to 99.99%, and the purity of the AlN powder is 99% to 99.99%.

5. The method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt according to claim 1, characterized in that: In the step S1, the rotation speed of the ball milling process is 100-400 r / min, and the ball milling time is 1-2 h.

6. The method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt according to claim 1, characterized in that: In step S2, the microwave heating power is 500-800 W, the microwave frequency is 2450±50 MHz, and the heating time is 10-30 min.

7. The method for efficiently preparing MAX phase metal carbonitrides using microwave molten salt according to claim 1, characterized in that: In step S3, the reaction temperature is 1100-1300° C., the heating rate is 30-50° C. / min, the insulation time is 5-30 min, the microwave heating power is 800-5000 W, the microwave frequency is 2450±50 or 915±50 MHz, and the protective atmosphere is argon or nitrogen.

8. The method for efficiently preparing MAX phase metal carbonitride from microwave molten salt according to claim 1, characterized in that At: In step S4, the drying is carried out in a blast drying oven at a temperature of 60 to 90° C. for a drying time of 30 to 60 minutes. The residual water content in the material after drying is 1-3%.

Citation Information

Patent Citations

  • Ti3AlC2 powder and preparation method thereof

    CN110817875A

  • Preparation method and application of novel nitrogen-containing MAX phase material and two-dimensional material

    CN114180969A

  • Hollow MAX phase powder with controllable morphology and preparation method thereof

    CN114772598A

  • Universal method for rapidly preparing MAX-phase or MAB-phase material

    CN116495735A

Cited By

  • Method for producing a fiber with MAX phases

    DE102025112133A1